PENILAIAN KONDISI PERKERASAN JALAN PADA RUAS JALAN AMAHUSU-LATUHALAT KOTA AMBON - Carlos Lekatompessy; Sammy G. M. Amaheka; Febrino Wangean (Pusat Penelitian dan Pengabdian Kepada Masyarakat (P3M) Politeknik Negeri Ambon, 2026)
The development of reliable road infrastructure serves as a key pillar in supporting regional connectivity, logistics distribution, and economic growth. In Indonesia, connectivity improvement policies have become a priority in the National Medium-Term Development Plan (RPJMN) 2020–2024 as an effort to accelerate equitable development, particularly in underdeveloped and archipelagic areas. This study aims to evaluate the pavement condition and determine the level of damage severity on the Amahusu–Latuhalat road segment in Ambon City using the Pavement Condition Index (PCI) method based on ASTM D6433. In addition, this study seeks to identify the distribution of pavement condition categories and propose appropriate maintenance strategies based on the obtained PCI values. The results indicate that the average PCI value of the 20 observed segments is 77.1, which falls into the “Good” category. The distribution shows that 35% of segments are in “Very Good” condition, 40% in “Good,” 10% in “Fair,” and 15% in “Poor.” These findings indicate that the pavement is still functionally adequate, although localized deterioration has occurred in several segments. Therefore, periodic maintenance and targeted rehabilitation are required to maintain pavement performance. Keywords: Pavement Condition Index; Road damage; Flexible pavement; Ambon City; Road maintenance